Relationship Between Bedroom Air Temperature and Blood Sugar Levels in Diabetes Mellitus Sufferers - Muhammad Rayhan Maulana Muslim; Yesi Hasneli; Nurhannifah Rizky Tampubolon (Journal of Education Technology Information Social Sciences and Health, 2024)
Introduction: Diabetes Mellitus is a chronic disease that occurs when the body cannot use insulin produced by the pancreas effectively. Diabetics suffer from complications in regulating the body's thermoregulation. The aim of this study was to determine the relationship between bedroom air temperature and blood sugar levels in diabetes mellitus sufferers. Method: Quantitative research with a cross-sectional approach. The research sample consisted of 95 respondents taken based on inclusion and exclusion criteria using simple random sampling techniques. The instruments used are thermohygrometer and glucometer. The analysis used was the chi-square test analysis. Results: Univariate analysis found that air temperature had a normal value of 30 oC, in bedroom air temperature there were 78 respondents categorized as abnormal (mean = 31.56 oC), blood sugar levels had a normal value of 200 mg/dL, 63 respondents were found to have high blood sugar levels (mean = 227.39 mg/dL). The air temperature in an abnormal bedroom has a 6,960 times greater risk of causing high sugar levels compared to the air temperature in a normal bedroom. The results of statistical tests show that there is a significant relationship between bedroom air temperature and blood sugar levels in diabetes mellitus sufferers. In this study, p-value (0.000) α (0.05) was obtained. Conclusion: The higher the bedroom air temperature ( 30 oC), the higher the blood sugar levels in diabetes mellitus sufferers.